PENGARUH INFLUENCER, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SKINCARE SKINTIFIC DI TIKTOK - Karinda, Revi Maikel; Fajri, Ariandi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Skintific is very active in promoting its products through social media. The social media that is often used by Skintific to promote its products is through the TikTok application. The decline can describe consumer behavior towards Skintific's purchasing decisions on the TikTok application. From the data above, the decline in purchases is a fairly serious problem, this must be addressed immediately so that it does not impact the company. This study aims to empirically prove Influencers, and Online Customer Reviews on Purchasing Decisions on Skintific Skincare Products on TikTok. The method in this study uses a quantitative method which is used to analyze the relationship between models by looking at which factors or variables can significantly influence the dependent variable. The population in this study is an infinite population which refers to customers who use Skintific Skincare beauty products where the number of population growth is unlimited and cannot be known for certain. The selection of samples in this study used the purposive sampling method, so that by using the Lemshow formula the sample obtained was 96.04. Thus, 100 respondents were considered representative enough to be studied. The results of this study state that Influencers have a significant positive influence on Purchasing Decisions on Skintific Skincare beauty products on the Tiktok Shop Platform. Online Costumer Reviews also have a significant positive influence on Purchasing Decisions on Skintific Skincare beauty products on the Tiktok Shop Platform.